MEMOTRET PENEGAKAN HUKUM DI INDONESIA - Fira Mubayyinah (Al Hikmah: Jurnal Studi Keislaman, 2016)
Indonesia is a state law. This is clearly contained in the state constitution, namely article 1, paragraph (3) of the Constitution of the Republic of Indonesia Year 1945. Explanation of the Constitution of the Republic of Indonesia Year 1945 further mentioned State Indonesia based on the law (rechstaat), not by power sheer (machtsstaat). As a country which proclaimed itself as a country of law, then all aspects of national life must be based on law. The emergence of dual obligation is related to several articles, namely: (a). Article 2, paragraph (1), which puts the Attorney as government agencies which implies that the prosecutor's office is an agency under the executive, but the authority to implement state power in the prosecution of running the judiciary; and (b). Article 19 paragraph (2) and Article 22 of the Attorney General is appointed, dismissed and responsible to the president, it is structurally under the executive judiciary but functionally is that in carrying out its functions should remain in line with the government-run legal politics.